1995
DOI: 10.1002/j.1460-2075.1995.tb06984.x
|View full text |Cite
|
Sign up to set email alerts
|

Human RPB5, a subunit shared by eukaryotic nuclear RNA polymerases, binds human hepatitis B virus X protein and may play a role in X transactivation.

Abstract: The X gene of human hepatitis B virus encodes the polypeptide HBx which transactivates viral and host genes through a variety of cis‐acting enhancer elements present in RNA polymerases I, II and III promoters. To better understand the mechanism of X transactivation, we cloned cDNAs of proteins that bind HBx. Here we demonstrate that one of these cDNAs is a full‐length cDNA of human RPB5, a subunit shared by RNA polymerases. The HBx transactivation domain and the central region of human RPB5 were necessary for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
215
0
2

Year Published

1996
1996
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(224 citation statements)
references
References 33 publications
7
215
0
2
Order By: Relevance
“…HBx does not directly bind to DNA and may stimulate transcription by interacting with transcription factors or with the basal transcription machinery of host RNA polymerase II and III (Cheong et al, 1995;Haviv et al, 1998;Maguire et al, 1991;Qadri et al, 1996;Williams and Andrisani, 1995). Besides its nuclear function as a transcriptional transactivator, several studies indicated that HBx in¯uences cellular signaling pathways in the cytoplasm as well, which is a function consistent with the predominant cytoplasmic localization of HBx in vivo and in most experimental systems (Benn and Schneider, 1994;Natoli et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…HBx does not directly bind to DNA and may stimulate transcription by interacting with transcription factors or with the basal transcription machinery of host RNA polymerase II and III (Cheong et al, 1995;Haviv et al, 1998;Maguire et al, 1991;Qadri et al, 1996;Williams and Andrisani, 1995). Besides its nuclear function as a transcriptional transactivator, several studies indicated that HBx in¯uences cellular signaling pathways in the cytoplasm as well, which is a function consistent with the predominant cytoplasmic localization of HBx in vivo and in most experimental systems (Benn and Schneider, 1994;Natoli et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the cellular pathways targeted by the viral protein to achieve transcriptional transactivation are a matter of debate. Indeed, in several studies, X has been reported to directly act on the transcriptional machinery (Cheong et al, 1995;Haviv et al, 1996;Lin et al, 1998;Maguire et al, 1991). In others, X appears to act far more upstream, by modulating the signal transduction cascade in the cytoplasm (Benn et al, 1996;Chirillo et al, 1996;Henkler et al, 1998;Kekule et al, 1993;Klein and Schneider, 1997;Lee and Yun, 1998;Su and Schneider, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The 16.5 kDa HBx protein is a multifunctional transactivator which up-regulates a variety of viral and cellular genes through protein ± protein interactions. In the nucleus, HBx may function as a co-activator by interacting with elements of the transcription machinery (Cheong et al, 1995;Haviv et al, 1998;Qadri et al, 1995), and from cytoplasmic locations by activating Ras/Raf signaling and NF-kB (Benn and Schneider, 1994;Cross et al, 1993;Natoli et al, 1994;Su and Schneider, 1996).…”
Section: Introductionmentioning
confidence: 99%